Polyphony of the Inhuman: Delirio, by Laura Restrepo - Barquero Matamoros, Daniela (2021)
The novel Delirium, by Laura Restrepo, displays a series of dehumanized characters. Thus, the construction of the actants in the novel is analyzed, by examining their representation through the rhetorical-stylistic resources of the social subjects. A description is provided of the interdiscourses that configure and define the sociocultural functions of the characters’ discourse. This is done from a socio-critical approach, with the support of critical discourse studies.